SUPPORTING PARENTS OF A SICK NEWBORN - Sanja Zupančič; Albina Gubanc; Jana Kodrič (The Society for Children with Metabolic Disorders, 2024)
Admission to the neonatal care unit is a distressing experience for parents. They often feel a sense of loss and mourn for the expected healthy child or the lost moments of pregnancy in the case of a premature birth. Supporting parents of a sick newborn is critical not only for their own mental health, but also due to potential implications for their relationship with their infant and subsequent child development. This review draws from current published clinical guidelines developed to support parents of a sick newborn. A holistic approach is recommended, including various professional profiles with an emphasis on educating parents and encouraging them to participate in the care of the newborn. Emphasis should also be on the importance of individual psychosocial support and support groups in alleviating stress and helping parents adjust to life with a sick child.